2015 ASEE Annual Conference and Exposition Proceedings
DOI: 10.18260/p.24503
|View full text |Cite
|
Sign up to set email alerts
|

Modifying the Student's Resistance Towards Active Learning with More Active-learning

Abstract: The application of methodological innovations in the teaching of engineering has been promoted and justified for several years now, especially those based on active learning and problem-based learning. However, the adoption of these new methodologies by universities has been slower than expected. Although many of the indicated causes refer to resistance by professors (e.g. a lack of time for implementation), there are also those that are based on resistance by students. In particular, an attitude of distrust i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…When comparing student-and instructor-centered pedagogies in an electrical engineering class, Yadav et al (2011)found that learning gains were highest in problem based learning sessions, despite students' beliefs that traditional lectures were most effective. Promising however, Recabarren et al (2015) reported that student preference for pedagogies depended to some extent on the practices they had been exposed to in the past. Although students engaged primarily in instructor-centered courses tended to prefer these traditional teaching methods, student preference changed after experiencing student-centered courses (Recabarren et al, 2015).…”
Section: Pedagogical Reformmentioning
confidence: 99%
See 3 more Smart Citations
“…When comparing student-and instructor-centered pedagogies in an electrical engineering class, Yadav et al (2011)found that learning gains were highest in problem based learning sessions, despite students' beliefs that traditional lectures were most effective. Promising however, Recabarren et al (2015) reported that student preference for pedagogies depended to some extent on the practices they had been exposed to in the past. Although students engaged primarily in instructor-centered courses tended to prefer these traditional teaching methods, student preference changed after experiencing student-centered courses (Recabarren et al, 2015).…”
Section: Pedagogical Reformmentioning
confidence: 99%
“…Promising however, Recabarren et al (2015) reported that student preference for pedagogies depended to some extent on the practices they had been exposed to in the past. Although students engaged primarily in instructor-centered courses tended to prefer these traditional teaching methods, student preference changed after experiencing student-centered courses (Recabarren et al, 2015). Overall, although student-centered courses have been shown to enhance student learning, students' unfamiliarity with the innovative teaching practices may lead to resistance or distrust.…”
Section: Pedagogical Reformmentioning
confidence: 99%
See 2 more Smart Citations
“…The survey was utilized to understand what actions students take in order to be successful in their classes, regardless of the instructor or the instructor's teaching style. Several researchers have investigated student success related to learning style and preferential presentation from an instructor in conjunction with student learning styles 13,[16][17][18] . However, Wankat and Oreovicz found that, regardless of a student's learning style or intelligence, motivation fundamentally controls whether or not a student learns 19 .…”
Section: Focus Of the Studymentioning
confidence: 99%